Exploring life patterns using entheseal changes in equids: Application of a new method on unworked specimens. (5th September 2019) - Bindé, Marion; Cochard, David; Knüsel, Christopher J.
Abstract: Understanding changes in the relationships between humans and horses through time and across geographic space is of great interest for researchers due to the fundamental economic, social, and symbolic importance of the horse for human societies. Altered muscular or ligamentous attachments serve as a means to explore this subject. Entheseal changes (ECs) are widely employed in biological anthropology for reconstructions of past activity patterns in human groups. This kind of analysis is far more rare in zooarchaeology, but interest has been increasing over the past decade, particularly for reindeer and equid remains. This contribution introduces a new recording protocol focused on 23 entheses located on the equine appendicular skeleton. In this contribution, this protocol is applied to unworked equids of various species and from diverse contexts in order to develop a baseline to gauge the extent of such changes for broad archaeological application. Bone formation and erosion of the surface of the attachment and, in some cases, its margins are considered. Intraobserver and interobserver tests reveal a general level of agreement of between 70% and 80% with variations from one enthesis to another. Examination of 27 complete skeletons of captive equids with no history of human use is investigated here to identify possible confounding factors, apart from activity, that influence the development of ECs. This study shows ECs to be age‐related and influenced by sexual dimorphism. Both aetiologies must be considered in future analyses. Some attachments in these specimens appear not to be influenced by sex and/or age at death, and this is promising. It is clear, however, that further studies of equids with documented activities are necessary to achieve a better appreciation of the factors responsible for the appearance of ECs before being applied to archaeological remains.